INTERNATIONALISATION OF HIGHER EDUCATION THROUGH ENGLISH AS A MEDIUM OF INSTRUCTION: THE UK EXPERTS’ VIEW - Modestova, Tetiana (Studies in Comparative Education, 2017)
The problem of the higher education internationalisation through English as a medium of instruction (EMI) on the basis of studying HE British experts’ view is considered in the article. The “higher education internationalisation” term is identified as a two-way process which includes intercultural and educational exchange. It includes the following aspects, which are expected to open wider opportunities for participants of educational process at higher school: international projects, participation in international educational interaction, student and university staff mobility as well as transparent academic and educational space. The importance of launching cooperation with governmental bodies, politicians, heads of universities, academic and teaching staff, Ukrainian and international students has been justified. The relevance of English has been agreed as a compliance criteria and a key tool for achieving the mentioned above goals. The model of policies for university internationalisation and the promotion of English as a medium of instruction has been characterized according to the following levels: national policy; institutional policy and planning. The following factors have been identified as the key ones: administrative initiatives, staffing initiatives, resource initiatives, infrastructure initiatives. The represented model is considered as a basis for further development of Ukrainian educational area in accordance with the recommendations given by the British experts for each level of the higher educational system (systemic and institutional) and for each of the staff groupings (management and EMI teachers). The ways for practical implementation of those recommendations (aimed at initiating correspondent initiatives and getting proper expert support at international level) through integration of Ukrainian universities into international projects have been identified.